(untitled) (Atenas, 2021)
Training for secondary school teachers is a stimulus for the education transformation and it prepares the individuals for more activity and the flourish of their talents and creates a wide range of necessary skills and ideas for teaching. The aim of this study is to investigate the in-service training course which is based on the problem-solving approach in high school mathematics, and to measure the quality of education, using Kirkpatrick’s four levels. Therefore, using a semi-experimental method, the problem-based training course was implemented for 62 male and female secondary school mathematics teachers. In this study, we used the questionnaire of in-service training course effectiveness evaluation which was developed based on Kirkpatrick’s evaluation model. To analyze of the research, R software was used. The results showed that with regard to the t-test for the significance of each of these paths, the effects of these paths are significant (p <0.01). Therefore, the teacher’s proficiency, academic ability and skill in choosing the best teaching method, holding training courses in an interesting and stimulating environment, using formative assessment to ensure the effectiveness of the training courses, are the issues that must be considered in mathematics teaching.